Strategi Komunikasi Pasangan Tuli dan Dengar dalam Menjalin Hubungan Romantis - EL Fatich, Hervita (Universitas Brawijaya, 2022)
Humans are social beings who cannot be separated from other individuals. Humans will always live side by side and communicate with other people. Interpersonal communication is needed by someone in order to learn about the external world and build relationships with other people, including the Deaf. The Deaf communicate by non-verbal or sign language. Communication also used by individuals to establish romantic relationships, in which there are communication strategies to solve problems. In this study, the method used is phenomenology to find out the communication strategies of deaf and hearing couples in establishing a romantic relationship. The results obtained are 1) Communication strategies that continues to develop in a more intimate direction, which begins with an approach process to recognize attitudes and compatibility with one another; 2) Communication gaps often arise in interpreting messages as the main obstacle in a process of communication between deaf and hearing couples; 3) Build trust between deaf and hearing partners by mutually disclosing information about themselves to their partners, because a sense of trust and comfort has arisen.